The inverted-U model of employee happiness: examining overdose happiness in context of personal characteristics, job-relationship dependency, benign stress, and various theories - Kalfaoğlu, Serap (Frontiers in Psychology, 2024)
In recent years, the management literature has begun to deal with individual and organizational results after happiness rather than the pursuit of happiness in business life and finally reaching happiness. After the fact that everything in an overdose is harmful, it has become the subject of even more research with paradoxical results that happiness that evokes positive emotions is not as innocent as it seems. In this study, which aims to reveal the harmful effects of overdose of employee happiness, the reasons for the manager’s fear - or anxiety - about the happiness of his employees are interpreted. The Inverted-U Model of Employee Happiness (IUMEH) has been developed and individual work outputs have been evaluated in three areas that (1) support happiness, (2) reflect balanced happiness, and (3) turn negative with an overdose of happiness intoxication. It has been suggested that IUMEH, which is thought to contribute to the literature as it is the first descriptive model to emerge, should be supported by applied studies, and it has been reminded that the curvilinear aspect of the model may include differences in terms of culture, type and characteristics of job, private, public or non-profit enterprises, generations of managers and the level of managers (front-line, middle level and senior level etc.).